An Experimental Study of The Effectiveness PEOW MODEL Through Applying Quartet Card in Teaching English Writing - Mandra Saragih; Novimariono Novimariono (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
This research deals with an experimental research in which aimed to investigate the effectiveness POEW model assisted Quartet Card in teaching English writing of recount text. The population and the sample of this research are the students of SMP Muhammadiyah 01 Medan academic year 2019/20120, on Jalan Demak No. 3, Sei Rengas Pertama, Medan Area. There are seven classes of garde VIII totally 270 students in which there are only 2 classes were taken as the sample of the research. The two classes are taught through two different model, the experimental class is taught through POEW model assisted Quartet Card and the control class is taught through lecturing Model. The essay test is applied for exploring the effectiveness of applying the model and it finally found that tobserve (4.67) was higher than ttable (2.01) with the degree of freedom (df=58). It means that the alternative hypothesis (Ha) was accepted. In conclusion, the POEW model assisted Quartet Card can effectively promote students’ English writing in recount text.